A latent profile analysis of the functions of binge eating - Elyse O’Loghlen; Roslyn Galligan; Sharon Grant (Journal of Eating Disorders)
Abstract Objective The aim of this study was to identify naturally occurring groups of individuals experiencing binge eating (BE) symptoms based on their endorsement of varied functions of BE. Method Adults (N = 646) with self-reported BE symptoms were examined using latent profile analysis to identify differentiated profiles based on eight established functions of BE. Profiles were also compared on measures of BE symptoms, eating disorder psychopathology, internal shame, body shame, psychological distress, adverse childhood experiences, and demographic variables. Results A four-profile solution was selected balancing goodness-of-fit and interpretability. Profiles identified were Emotion Avoidance, Classic, Emotion Reactivity, and Complex, with profiles differing primarily on emotion- and trauma-related functions of BE, and varying on all associated characteristics examined, with the Complex profile showing the most adverse associations. Discussion The identification of these distinct profiles suggests that individuals present with differentiated, inter-related patterns or reasons for BE. These clinically relevant profiles may inform binge-eating intervention choice and the targeting of specific maintenance factors within profiles. Further research is needed to examine the clinical utility of these profiles in informing the most suitable psychological treatment for an individual.